1,8-Cineole Ameliorates LPS-Induced Vascular Endothelium Dysfunction in Mice via PPAR-γ Dependent Regulation of NF-κB - Linghu, Ke-Gang; Wu, Guo-Ping; Fu, Ling-Yun; Yang, Hong; Li, Hai-Zhi; Chen, Yan; Yu, Hua; Tao, Ling; Shen, Xiang-Chun (Frontiers in Pharmacology, 2019)
1,8-Cineole (eucalyptol), a monoterpene, has been widely reported for the anti-inflammatory effects. Our previous data confirmed that 1,8-cineole ameliorated the inflammatory phenotype of human umbilical vein endothelial cells (HUVECs) by mediating NF-κB expression in vitro. At present, we investigated the protection effects of 1,8-cineole on vascular endothelium in lipopolysaccharide (LPS)-induced acute inflammatory injury mice and the potential mechanisms involved in the protection in HUVECs. Results from enzyme linked immunosorbent assays revealed that 1,8-cineole suppressed the secretion of interleukin (IL)-6 and IL-8 and increased the expression of IL-10 in the serum of LPS-induced mice. 1,8-Cineole reduced the inflammatory infiltration and the expression of vascular cell adhesion molecular 1 (VCAM-1) in the sections of thoracic aorta in LPS-induced acute inflammatory mice. Western blotting indicated that 1,8-cineole significantly decreased the phosphorylation of NF-κB p65 and increased the expression of PPAR-γ in the thoracic aorta tissue. 1,8-Cineole increased the expression of PPAR-γ in LPS-induced HUVECs. 1,8-Cineole and rosiglitazone reduced the protein and mRNA levels of VCAM-1, E-selectin, IL-6 and IL-8 in LPS-induced HUVECs, which could be reversed by the action of GW9662 (inhibitor of PPAR-γ). 1,8-Cineole and rosiglitazone blocked the LPS-induced IκBα degradation and NF-κB p65 nucleus translocation, which could be reversed by the pretreatment of GW9662 or silence of PPAR-γ gene. In conclusion, 1,8-cineole attenuated LPS-induced vascular endothelial cells injury via PPAR-γ dependent regulation of NF-κB.